THE IMPLEMENTATION OF MATERIAL CRIMINAL LAW TOWARD THE CRIME OF TRAFFICKING IN PERSONS - Warsifah, Warsifah; Mangatur , Julius (IBLAM LAW REVIEW, 2021)
The unbalanced and unequal economic growth in society often creates social and social jealousy in the community. On the one hand, there is a group of people who have sufficient capacity economically, but on the other hand there is a group of people who have no economic capacity in their lives, so that the latter group is often a social problem that even commits the crime of theft, for example. The criminal act of theft according to the Criminal Code, there is an element of "burdensome" as regulated in Article 363 paragraph (1) of the 5th Criminal Code, namely: "It is punished with a maximum imprisonment of seven: Theft committed by a wrongdoer by entering the place. the crime or it can reach the goods to be taken, such as the example of the case presented by the author in this thesis research, namely the theft of a helmet which was committed by the defendant, preceded by the defendant entering the campus environment, the case of which was decided by the Sukabumi District Court with a decision Number: 17 / Pid. B / 2010 / PN. Skh. The formulation of the problem that will be discussed by the author are: 1) How is the application of material law to the perpetrator of the crime of theft with weighting? and 2) How is the law enforcement against the perpetrators of the crime of theft of a helmet with a weight as in Court Decision Number 17 / Pid.B / 2010 / PN. Skh? The research method that the author uses is the normative juridical method, meaning that the data used comes from library research, carried out by searching, quoting, taking notes, inventorying, analyzing, and studying data in the form of library materials needed and related to law enforcement against perpetrators. theft by weight. Finally, based on the results of the research, the authors conclude that law enforcement against the perpetrators of the crime of theft of a helmet with a weight as in Court Decision Number 17 / Pid.B / 2010 / PN. Skh, the defendant was threatened with article 363 paragraph (1) to 5 of the Criminal Code, so that the defendant Agus Hery Santoso Bin Diyono was found legally and convincingly guilty of committing a criminal act. for 2 (two) months and 15 (fifteen) days.